Antibacterial Efficacy of Several Surgical Hand Preparation Products Used by Veterinary Students. Issue 4 (May 2016) - Chou, Po‐Yen; Doyle, Aimie J.; Arai, Shiori; Burke, Pierre J.; Bailey, Trina R.
Abstract : Objective: To compare the antibacterial efficacy of different surgical hand antisepsis protocols used by veterinary students. Study Design: Prospective, randomized, controlled study. Study Population: Third year veterinary students (n=45). Methods: The participants were randomly assigned to 4 of the following 12 hand preparation product/time combinations: nonabrasive hand scrub method with 4% chlorhexidine gluconate (CH); hand rub with a mixture of 30% 1‐propanol and 45% 2‐propanol solution (MPS), 70% 2‐propanol solution (IPS), or 61% ethanol solution with 1% chlorhexidine gluconate (ES/CH), with a contact time of 1.5, 3, or 5 minutes. Antibacterial efficacy was assessed after surgical hand preparation and at the end of surgery. Log reductions of total bacterial colony forming unit (CFU)/mL and positive aerobic culture rates were compared using multivariable analysis of variance and multivariable logistic regression, respectively. Results: After surgical hand preparation, CH and ES/CH provided significantly higher log CFU reduction and lower positive culture rate for Gram‐positive and spore‐forming bacteria compared to MPS and IPS. Increase in contact time did not provide significant improvement in bacterial reduction. At the end of surgery, ES/CH provided significantly higher log CFU reduction compared to IPS and lower positive culture rate for Gram‐positive bacteria compared to CH, MPS, and IPS. Increase in contact time significantly improved log CFU reduction in ES/CH and MPS groups. Conclusion: In our population of veterinary students ES/CH hand rubs or CH scrubs were more effective in reducing bacterial CFU during surgical hand preparation than MPS or IPS.